A low-cost wearable yarn supercapacitor constructed by a highly bended polyester fiber electrode and flexible film. Issue 29 (10th July 2017) - Zhang, Si-Wen; Yin, Bo-Si; Liu, Chang; Wang, Zhen-Bo; Gu, Da-Ming
Abstract : For the next-generation energy-storage devices, high power density supercapacitors can be used as complementary power supplies. Abstract : For the next-generation energy-storage devices, high power density supercapacitors can be used as complementary power supplies. However, the shortcomings such as low energy density, complicated synthesis process, and high cost have limited their wide applications. Moreover, their rigid bulk structures hinder their applications in wearable electronics. Herein, we developed a fiber-shaped supercapacitor (FSC) with a volumetric energy density of up to 7.9 mW h cm −3 and volumetric capacitance of 28.8 F cm −3 . This new FSC consists of a self-supported hybrid film electrode and free-standing polyester fiber electrode that are prepared using simple hydrothermal and vacuum filtration methods, respectively. The FSC also has high flexibility under different bending degree tests and long cycle life (capacitance retention efficiency is 98.6% after 10 000 cycles). Based on the abovementioned discussion, it can be concluded that this new type of FSC with the advantages of low-cost, high flexibility, ultrahigh energy density, and ultralong cycle life will play an important role in many fields and is expected to act as a new star in the energy storage devices.